Data sharing to advance gene‐targeted therapies in rare diseases. Issue 1 (3rd January 2023) - Lekstrom‐Himes, Julie; Augustine, Erika F.; Brower, Amy; Defay, Thomas; Finkel, Richard S.; McGuire, Amy L.; Skinner, Mark W.; Yu, Timothy W.
Abstract: Recent advancements in gene‐targeted therapies have highlighted the critical role data sharing plays in successful translational drug development for people with rare diseases. To scale these efforts, we need to systematize these sharing principles, creating opportunities for more rapid, efficient, and scalable drug discovery/testing including long‐term and transparent assessment of clinical safety and efficacy. A number of challenges will need to be addressed, including the logistical difficulties of studying rare diseases affecting individuals who may be scattered across the globe, scientific, technical, regulatory, and ethical complexities of data collection, and harmonization and integration across multiple platforms and contexts. The NCATS/NIH Gene‐Targeted Therapies: Early Diagnosis and Equitable Delivery meeting series held during June 2021 included data sharing models that address these issues and framed discussions of areas that require improvement. This article describes these discussions and provides a series of considerations for future data sharing.